(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Marketers have been using electronic tools for many years, but the Internet and other new technologies created a flood of interesting and innovative ways to provide and enhance customer value. Not only did this challenge the fundamental basics of traditional marketing, but it also helped to shape the practice of modern marketing The advancement of technology has not only created new ways for marketers to spread information, but also enabled consumers to spread information on-line or through other digital mediums that challenge traditional marketing practices. Since viral marketing is still a new and unexplored concept for most of the markets, it is the purpose of this article to determine if it is not just another buzzword. To establish if marketers can practice viral marketing, the concept of viral marketing is clarified before addressing more specific issues related to it. We present an analysis of a person-to-person recommendation network, on a lot of products. We observe the propagation of recommendations and the cascade sizes, which we explain by a simple stochastic model. We analyze how user behavior varies within user communities defined by a recommendation network. Product purchases follow a ’long tail’ where a significant share of purchases belongs to rarely sold items. We establish how the recommendation network grows over time and how effective it is from the viewpoint of the sender and receiver of the recommendations. While on average recommendations are not very effective at inducing purchases and do not spread very far, we present a model that successfully identifies communities, product and pricing categories for which viral marketing seems to be very effective.